Determinants Of Stock Split With Dividend Policy As A Moderating Variable In Companies Listed On The Indonesian Stock Exchange - Sarah Sinadela; Ratih Kusumastuti; Nela Safelia (Cita konsultindo, 2025)
This study aims to analyze the factors influencing companies to undertake stock splits and examine the role of dividend policy as a moderating variable in the relationship between these determinants and stock splits. The independent variables used in this study include abnormal returns, trading volume activity, stock price, bid-ask spread, and market performance. Dividend policy is moderated using the dividend payout ratio. This study was conducted on companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Data were obtained through documentation methods from annual financial reports and market data published by the IDX. The sample selection was conducted using purposive sampling, with a sample size of 168 companies. The analytical method used was moderated regression analysis to test the direct and interaction effects between variables using SPSS 30 software. The results showed that abnormal returns, trading volume activity, stock price, and market performance significantly influenced stock splits, while the bid-ask spread had no direct effect. Dividend policy is shown to moderate the relationship between abnormal returns and stock prices but does not moderate the relationship between trading volume activity, bid-ask spread, and market performance with stock splits. This finding suggests that companies consider market signals and dividend strategies simultaneously when making stock split decisions. This research provides theoretical contributions to the corporate finance literature and provides practical implications for investors and company management in understanding stock and dividend policy strategies in the Indonesian capital market.